ROBOT CLUSTER DEVELOPMENT POLICY IMPLEMENTATION - Abhinorasaeth, Chakrit; Kalyanamitra, Kamolporn; Niyomyaht, Satit; Lakkanapichonchat, Tassanee (Journal of Educational Review Faculty of Education in MCU, 2021)
The purpose of this research was to 1) to study the robot cluster development policy implementation and 2) to study problems and obstacles to robot cluster development policy implement. This research was a qualitative research. This was a method that could gain insights into weight. reliability from key informants who had chosen a purposive selection from knowledgeable people. expertise, experience and strong relevance in the robotics industry, including senior government executives, middle-level government executives, entrepreneurship association, executive level of the private sector, government academics, scholars in the government and private sectors, totaling 19 key informants. The results found that: 1) Thailand industrial needs aimed to develop and promote robot clusters. It aimed that B.E.2026 will be the leading exporter of robots and automation in the ASEAN region. Robot development according to industrial needs to encourage robotics and automation operators to develop products that were responsive to the agricultural service, pharmaceutical, beverage, food processing, logistics, automotive and electrical and electronic sectors. Promotion and development of the potential of Thai people in the production of robots. Integrating cooperation between various institutions to develop skills and academics promoting and driving teaching and learning curriculum, creating and developing competent teachers to produce personnel to drive in the robot industry. Enhancing the capability of the country to produce Thai robots with human resource development, dissemination of knowledge in robotics and automation technology, establishment of a specific agency, establishing network partners, promoting investment in various industrial sectors. Mutual investment measures between manufacturers, government and financial institutions by the user side had tax investment measures for business that adopt automation and robots to improve production efficiency. The manufacturers had exempted tariffs on robotic parts and automation. Government funding and domestic financial institutions providing benefits to businesses that used robots and automation and was a category that the BOI promotes and free funds. Tax measures by providing tax incentives user tax measures include income tax deductions, corporate income tax exemption. And tax measures for manufacturers included the corporate income tax exemptions. 2) Problems and obstacles were problems of lack of cooperation between various sectors. Thai manufacturing sectors were not concerned with the introduction of automation and robots, lack of knowledgeable, competent and skilled personnel, unable to develop on their own systems, technology, robots and automation of high complexity.